+0  
 
0
208
1
avatar+1015 

Simplify the expression . Show your work.

AngelRay  Jan 17, 2018

Best Answer 

 #1
avatar+17736 
+1

Simplify:  sqrt( 4x2 / 3y )

 

                sqrt( 4x2 / 3y )  =  sqrt( 4x2 ) / sqrt( 3y )

 

But  sqrt( 4x2 )  =  2·| x |                                  Technically, you need to use absolute value bars.

 

               sqrt( 4x2 / 3y )  =  2·| x |  / sqrt( 3y )

 

Now, multiply both the numerator and the denominator by sqrt( 3y )

 

              sqrt( 4x2 / 3y )  =  [ 2·| x | · sqrt( 3y) ] / [ sqrt( 3y ) · sqrt( 3y) ]

 

Since  [ sqrt( 3y ) · sqrt( 3y) ]  =  3y

 

               sqrt( 4x2 / 3y )   =  [ 2·| x | · sqrt( 3y) ] / ( 3y )

geno3141  Jan 17, 2018
 #1
avatar+17736 
+1
Best Answer

Simplify:  sqrt( 4x2 / 3y )

 

                sqrt( 4x2 / 3y )  =  sqrt( 4x2 ) / sqrt( 3y )

 

But  sqrt( 4x2 )  =  2·| x |                                  Technically, you need to use absolute value bars.

 

               sqrt( 4x2 / 3y )  =  2·| x |  / sqrt( 3y )

 

Now, multiply both the numerator and the denominator by sqrt( 3y )

 

              sqrt( 4x2 / 3y )  =  [ 2·| x | · sqrt( 3y) ] / [ sqrt( 3y ) · sqrt( 3y) ]

 

Since  [ sqrt( 3y ) · sqrt( 3y) ]  =  3y

 

               sqrt( 4x2 / 3y )   =  [ 2·| x | · sqrt( 3y) ] / ( 3y )

geno3141  Jan 17, 2018

24 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.